Perencanaan Bisnis Oleh-oleh dan Agrowisata di Kabupaten Grobogan Menggunakan Bussines Model Canvas - Mega Anggraeni Putri (Universitas Duta Bangsa Surakarta, 2021)
Grobogan Regency, is one of the regencies in Central Java Province. Grobogan Regency is a regency that is rich in plants, one of which is pumpkin, pumpkin which is abundant in Grobogan Regency during the main harvest, the price drops, so it is necessary to innovate so as to increase the value of pumpkin products. Pumpkin is processed to produce added value as a typical Grobogan souvenir. This study aims to analyze the strengths, weaknesses, opportunities, and threats based on the 9 elements of the Business Model Canvas and map out new strategies in order to increase sales of Pumpkin Cookies and their Agrotourism with the method used in this study through the Business Model Canvas (BMC) approach and SWOT analysis that produces a strategy matrix. The type of research used is observation and literature study. The results of this study indicate the business position in quadrant II on the SWOT diagram, and is represented visually using BMC. It can be concluded that this business has sufficient opportunities to develop by implementing the strategies proposed.